2016
DOI: 10.1007/s00234-016-1697-7
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic MR in patients affected by neurogenical claudication: technique and results from a single-center experience

Abstract: Dynamic MR is a valuable diagnostic exam to analyze the structures involved in lumbar back pain due to spinal canal stenosis and spondylolisthesis; in supine position, relevant factors can be underestimated or hidden, becoming appreciable only patient standing upright. In this series, flavum ligament thickening presented a role comparable to disc bulge for narrowing of lumbar spinal canal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
(55 reference statements)
1
10
0
Order By: Relevance
“…LSS is also a disease of the elderly who inherently carry a greater anesthetic risk. Minimally invasive and percutaneously inserted interspinous spacers have been shown to be both non-inferior in terms of patient outcomes and to have decisive benefits in terms of operating times and blood loss 2–26. This cohort of patients, the largest in a single study, confirms the existing cited literature which shows improvement in patient symptomatology and function after interspinous spacer insertion.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…LSS is also a disease of the elderly who inherently carry a greater anesthetic risk. Minimally invasive and percutaneously inserted interspinous spacers have been shown to be both non-inferior in terms of patient outcomes and to have decisive benefits in terms of operating times and blood loss 2–26. This cohort of patients, the largest in a single study, confirms the existing cited literature which shows improvement in patient symptomatology and function after interspinous spacer insertion.…”
Section: Discussionsupporting
confidence: 74%
“…This pathophysiology underpins the classical presentation of lumbar spinal stenosis (LSS): progressive back, buttock and lower limb pain which comes on rapidly with ambulation (when the patient is naturally more extended) and relieved by sitting or lying (when the patient is naturally flexed). The changes in the spinal canal and associated ligaments have been demonstrated on dynamic MRI studies 1–4…”
Section: Introductionmentioning
confidence: 99%
“…The wide availability of magnetic resonance (MR) imaging leads to a early diagnosis of radicular disc compression; furthermore, the introduction of dynamic MR studies has allowed to expand the analysis of the structures involved in lumbar back pain even in the less clear scenarios [8].…”
Section: R Esum Ementioning
confidence: 99%
“…However, bSSFP, as an excellent acquisition strategy for cardiac MRI, was never thoroughly evaluated at lower field strengths, despite several desirable features of lower field strengths. Low-field MRI has been receiving increasing attention since a study by Rutt et al (6) demonstrated that, for certain imaging applications, low-field MR images are diagnostically equivalent to images acquired at 1.5 T. In recent years, low-field MRI has seen application in open MRI systems (19,20), intraoperative MRI (21,22) and is (23,24). In anticipation of increasing applications of low-field MR, recently a study was published by Wu et al 7exploring the feasibility of low-field MR at various field strengths for compressed sensing applications.…”
Section: Discussionmentioning
confidence: 99%